Domestic Violence against Women: A Study of Nalbari District in Assam - Talukdar, Gitima (International Journal of Psychosocial Rehabilitation, 2020)
Domestic violence is a pattern of abusive behaviour in any relationship that is used by one partner to gain or maintain power and control over another partner. Domestic violence can happen to anyone regardless of race, age, caste, religion or gender. It is a Pattern of behaviour characterised by the misuse of power and promise by one person against another who generally happens to be in an intimate or blood relationship. Domestic violence may be of different kinds like physical violence, sexual abuse, emotional abuse, economic deprivation and stalking. Physical violence is the intentional use of physical force for causing injury, harm, disability or death to the victims. Physical violence is the easiest` to recognise and understand than any other types of domestic violence. Hitting, shoving, beating, restraining, kicking, scratching, pushing, slapping, punching or uses of a weapon are the few examples of physical violence.